The power of social networks: A model for weaving the Scholarship of Teaching and Learning into institutional culture (Teaching and Learning Inquiry, 2013)
This paper offers a guide for those seeking to integrate the Scholarship of Teaching and Learning (SoTL) into higher education institutions to improve the quality of student learning. The authors posit that weaving SoTL into institutional cultures requires the coordinated actions of individuals working in linked social networks rather than individuals acting in isolation. Analyzing both the barriers and potential pathways to integrating SoTL into institutional cultures, the authors provide a conceptual model along with examples of practical strategies for overcoming resistance to change within institutions. The paper provides examples from a variety of different international contexts to show how incentives and other non-coercive measures can motivate faculty and administrators to weave SoTL into institutional fabrics.Drawing on social network theory and the concept of communities of practice, the paper presents a model with attendant strategies for disseminating SoTL values and practices across all three levels of postsecondary institutions: the micro, the meso, and the macro. The authors argue that for SoTL to take root in organizational cultures, there must be 1) effective communication and dissemination of SoTL activity across all levels, 2) well established social networks and links between these levels (nodes), and 3) sustained support by senior administration. The authors conclude by suggesting ways their model could be tested.